A 'Ludicrous and Inappropriate' Dinner Guest:: The Character of the Titus Andronicus Fly - Odbert, Mary (Early Theatre, 2025)
This article proposes a new approach to Titus Andronicus's infamous ‘Fly-Killing Incident’ in act 3, scene 2 which prioritizes the role of the segmented fly as a character alongside the dismembered Andronici. Rejecting the critical tendency to read the diminutive figure as a passive emblem for interpreting humanity, this article explores the subjectivity of the fly as an individual with a particular focus on the implications of its murder and dismemberment. Whilst acknowledging its often-flippant critical history, this article asks, ‘What if we took the fly seriously’?